Influence of two different printing methods on the accuracy of full-guided implant insertion – a laboratory study in undergraduate dental students - Matthias C. Schulz; Michael Krimmel; Christina Weismann; Pablo Kaucher-Fernandez; Bernd Lethaus; Nils Kristian Mann (BDJ Open)
Abstract Objectives The aim of the present study was to compare the accuracy of fully guided implant insertion in vitro achieved by two fabrication methods in a cohort of undergraduates. We hypothesized that both methods achieve a comparable accuracy. Methods Surface scans and cone beam computed tomography images of 48 mandibular models were matched. For each model, two surgical guides enabling a fully guided implant insertion in the region of the first molar on the left or the right side were virtually designed. Fabrication by either Digital Light Processing (DLP) or Fused Filament Fabrication (FFF) followed. Subsequently, 96 implants using the guides were inserted into the models by 48 undergraduate students. The accuracy of the implant insertion was assessed radiographically, followed by statistical analysis. Additionally, all participants completed a questionnaire. Results The implants inserted using guides made by DLP showed a higher accuracy compared to guides made by FFF. The mean three-dimensional deviation was 1.94 ± 1.05 vs. 3.35 ± 2.03 degrees (p < 0.001). The evaluation of the questionnaires revealed mainly theoretical knowledge and a pronounced interest in implant dentistry. Discussion The main hypothesis has to be rejected as there were statistically significant differences in accuracy. However, it is possible to teach students the principles of guided implant dentistry and the digital workflow. Furthermore, the initial and running costs for the FFF workflow are substantially lower enabling a higher practicability for undergraduate education. Conclusion Despite the lower accuracy of the templates made from FFF the method seems to be suitable for laboratory hands-on courses for undergraduates.